Reserves Were Not So Ample After All - Copeland, Adam; Duffie, Darrell; Yang, Yilin (David) (Quarterly Journal of Economics, 2025)
Abstract We show that the likelihood of a liquidity crunch in wholesale U.S. dollar funding markets depends on levels of reserve balances at the financial institutions that are the most active intermediaries of these markets. Heightened risk of an imminent liquidity crunch is signaled by significant delays in intraday payments to these large financial institutions over the prior two weeks. Our study contributes to the broader dialogue surrounding the Federal Reserve’s ongoing quantitative tightening.